The Israeli Digital Diplomacy Directed to the Arabs: An Analysis of the “Israel speaks Arabic” Facebook Page - Shalash, Linda S. I. (Journal of Al-Tamaddun, 2023)
Due to advances in technology, foreign countries and their diplomats have resorted to social media to reach a wider and more global audience. Israel, like many others, has taken advantage of the digital world to improve its image in the Middle East. In fact, the Israeli Ministry of Foreign Affairs started a special department for digital diplomacy, which manages dozens of digital pages in multiple languages. This paper investigates the strategies that Israel has employed in its digital diplomacy in recent years to improve its image with its Arab neighbors by analyzing approximately 600 posts published on the Israeli Facebook page “Israel Speaks Arabic.” Results of the analysis reveal that the page employs many propaganda strategies to attract Arabs and earn their recognition and acceptance of Israel, such as positing digital publications in frameworks related to conflict, responsibility, and morality in a way that shows Israel as a rational, democratic, peace-loving state that cooperates with its Arab neighbors. “Israel Speaks Arabic” also employs persuasive means that address passion and desires using religion and the humanization of the occupation and its army. Other strategies include the manipulation of terminology, repetition, the amplification of events, and the employment of eminent Arabic voices against the Palestinians that serve Israel’s narrative at the expense of the Palestinian one. The article rests on framing theory.